From Farm to Finger Prick—A Perspective on How Plants Can Help in the Fight Against COVID-19 - McDonald, Karen A.; Holtz, R. Barry (Frontiers in Bioengineering and Biotechnology, 2020)
As a consequence of the COVID-19 pandemic crisis, farmers across the country are plowing under their fields and laying off workers. Plant biomass has been shown by the DARPA “Blue Angel” project in 2010 to be an efficient way to rapidly make vaccines and diagnostics. This technology could pivot some areas of agriculture toward biomedical products to aid in the COVID-19 pandemic response.